Mobile Health for Obsessive-Compulsive Disorder - Araújo, Ana Isabel (2025)
BACKGROUND: The increasingly fast development of mobile health technologies holds significant value for individuals dealing with mental health conditions. However, inadequate consideration of patients' preferences and expectations undermines real-world outcomes, including sustained adherence. Driven by the belief that specific characteristics, such as youth and higher education, of individuals with obsessive-compulsive disorder make them suitable for digital adoption, we investigated mHealth-related desirability factors within this patient group. METHODS: Fifty-one conveniently selected adults with obsessive-compulsive disorder filled in a self-report questionnaire about symptom self-management preferences, with an emphasis on assessing mobile health options and perceptions of patient-centeredness. RESULTS: The smartphone phone app emerged as the top choice of most of the sample for receiving information about symptom status (82.4%), obtaining general information about obsessive-compulsive disorder (74.5%), and symptom self-registration (66.7%), with no significant effect of sex or living location. Although only 23.5% of participants were using a health-related app, most expressed interest in using it for receiving symptom management tips (98.1%), medical advice (94.2%), symptom evolution updates (90.2%), lifestyle information (92.2%), medication tracking (88.2%) and short symptom self-reports (90.2%). Median expectations regarding mobile health's impact on patient-centeredness, satisfaction, and adherence were positive or very positive. CONCLUSIONS: Our data confirm that individuals with obsessive-compulsive disorder exhibit strong inclinations and optimistic expectations toward technology-based solutions. We highlight some of the preferences within this patient group, which can inform the design of practical, real-world applications.